Sosialisasi Persiapan Dana Pendidikan Anak - Putri Asrina; M Rizwan; Lapeti Sari (CV. Multi Kreasi Media, 2026)
Preparing education funds is crucial for ensuring a quality education for children. Providing a good education aligned with the family's vision and mission is a parental responsibility and a child's right to receive a proper education. Therefore, parents need to prepare a financial budget to realize their children's dreams, taking into account all their abilities. The purpose of this community service activity is to raise awareness and understanding among housewives in Sungai Sibam Village regarding preparing education funds for their children. This community service activity is carried out through a lecture method, providing information on the importance of preparing education funds for children, simulating the calculation of education funds for children, the steps that can be taken to start preparing education funds, and teaching various investment instrument options that can be used to manage children's education funds. Through this outreach activity, it is hoped that mothers who participate in the community service activity will begin to focus on preparing education funds for their children and then begin to understand the most appropriate investment instruments to choose according to the specified education period. Thus, with this outreach on education funds, it is hoped that parents will be able to provide the best education for their children and maintain healthy family finances without debt.